Improved QoS and avoidance of black hole attacks in MANET using trust detection framework. (3rd July 2019) - Manoranjini, J.; Chandrasekar, A.; Jothi, S.
ABSTRACT: In recent times, secured routing is a major research in MANETs. The behaviour of malicious nodes in this network increases the risk of threats and induces abnormal operations in MANETs. This affects the security of data transmitted between the nodes in the network. Hence, an effective technique is needed to prevent the abnormal nodes after the process of detection. In this paper, we propose an improved Trust Detection Algorithm to increase the probability of detection and prevention of Black Hole nodes in MANETs. The proposed framework observes the behaviour of each node using various trust metrics that includes the relationship between the sensor nodes, social and service attribute trust and QoS metric trusts. The behaviour of sensor nodes is found through the communication and mobility behaviour of each node. This method avoids the black hole nodes in MANETs, when the routing is carried out with Zone Routing Protocol (ZRP). Hence, the privacy of data is retained using the proposed method. The proposed method is tested in terms of different combinations of with and without trusts. The result shows that the proposed method is effective through various QoS metrics like overall throughput, packet loss, energy consumption, trust level, false acceptance rate and missed detection rate.